Impedance analysis of ASTM A416 tendon steel corrosion in alkaline simulated pore solutions. (March 2016) - Chen, Yu-Min; Orazem, Mark E.
Abstract : Highlights: After cathodic pretreatment, ASTM A416 steel shows porous electrode behavior. Approach to steady state conditions requires from one to three days. Impedance model accounted for contributions of both anodic and cathodic reactions. Oxide film thickness depends strongly on elapsed time. Abstract: The corrosion behavior of ASTM A416 steel in alkaline simulated pore solution under active aeration was studied by cyclic voltammetry, electrochemical impedance spectroscopy, and measurement of open-circuit potential and polarization curves. The electrochemical impedance spectra were interpreted by use of a model that accounted for porous electrode behavior and for the contributions of both anodic and cathodic reactions. The open-circuit corrosion rate for a stationary working electrode immersed in the active-aerated electrolyte was 64 μm/year shortly after the cathodic pre-treatment was completed, but was too small to be detected after steady-state was reached.